METHODOLOGY OF WORKING ON THE SPELLING OF PRONOUNS IN PRIMARY CLASSES - Husniddin kizi , Ergashova Mehriniso (PT. Antis International Publisher, 2024)
The significance of mastering proper nouns and their spelling in primary education is a critical area that warrants focused pedagogical strategies. General Background: Proper nouns serve as foundational elements in language acquisition, yet they are often overlooked in traditional curricula. Specific Background: This oversight presents challenges in developing students' literacy skills, particularly in recognizing and correctly spelling proper nouns. Knowledge Gap: Existing literature lacks comprehensive methodologies that blend theoretical approaches with practical exercises tailored to primary learners. Aims: This article aims to present innovative strategies for teaching proper nouns and their spelling, highlighting effective instructional methods and exercises. Results: Through the implementation of targeted activities and assessments, the findings suggest significant improvements in students' spelling proficiency and overall engagement with language tasks. Novelty: This study contributes a unique framework that integrates contemporary educational theories with hands-on practices, fostering a more interactive learning environment. Implications: The insights garnered from this research underscore the necessity of revising teaching methodologies to prioritize the spelling of proper nouns, ultimately enhancing literacy outcomes in primary education. By addressing the identified knowledge gap, this article serves as a resource for educators seeking to enrich their instructional practices and support students in mastering essential language skills.